ACOs Holding Commercial Contracts Are Larger And More Efficient Than Noncommercial ACOs - Peiris, David (Health Aff (Millwood), 2016)
Accountable care organizations (ACOs) have diverse contracting arrangements and have displayed wide variations in their performance. Using data from national surveys of 399 ACOs, we examined differences between the 228 commercial ACOs (those with commercial payer contracts) and the 171 noncommercial ACOs (those with only public contracts, such as with Medicare or Medicaid). Commercial ACOs were significantly larger and more integrated with hospitals, and had lower benchmark expenditures and higher quality scores, compared to noncommercial ACOs. Among all of the ACOs, there was low uptake of quality and efficiency activities. However, commercial ACOs reported more use of disease monitoring tools, patient satisfaction data, and quality improvement methods than did noncommercial ACOs. Few ACOs reported having high-level performance monitoring capabilities. About two-thirds of the ACOs had established processes for distributing any savings accrued, and these ACOs allocated approximately the same amount of savings to the ACOs themselves, participating member organizations, and physicians. Our findings demonstrate that ACO delivery systems remain at a nascent stage. Structural differences between commercial and noncommercial ACOs are important factors to consider as public policy efforts continue to evolve.